The Relationship Between Peer and Familial Social Support and Mental Well-Being of Indonesian College Students During the COVID-19 Pandemic - Ira Nurmala; Jayanti Dian Eka Sari; Farapti Farapti; Muthmainnah Muthmainnah; Dianna Suzieanna Mohamad Shah; Airil Haimi Mohd Adnan; Yuli Puspita Devi; Nisrina Auliyah Laras Karindra; Laila Wahyuning Tyas; Hadina Habil; Annisa Clara Salsabila (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Student mental well-being was a concern prior to the COVID-19 pandemic. During COVID-19, mental health problems increased due to heightened anxiety and concern. Family and friends' support plays a crucial role in maintaining students' mental health. This study examines the impact of social support on students' mental well-being during the pandemic. Methods: This analytic observational study employed a cross-sectional design with a total of 400 active student participants. Psychometric instruments used in this study were the Sallis Social Support Scale and the short version of the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS-7). Data were analyzed using Spearman correlation to determine the relationship between family and friends' support and students' mental well-being. Results: There was no significant relationship between family support and students’ mental well-being. However, only support from friends showed a statistically significant positive relationship with students' mental well-being (r = 0.176, p = 0.001), while support from family was not significantly associated (p = 0.073). Conclusion: Social support from friends played a crucial role in maintaining students' mental well-being during COVID-19. Encouraging peer support, such as reminding each other to complete tasks, can positively influence mental health.